2011
DOI: 10.3109/13697137.2010.495423
|View full text |Cite
|
Sign up to set email alerts
|

Women's perception of the menopause and hormone treatment: barriers against hormone therapy

Abstract: The treatment of half of the women who used HT was terminated by doctors, while the other half chose to discontinue the therapy themselves due to their fear of cancer. The present study offers a significant insight into the barriers against HT for women in the menopausal period. Health professionals should inform women about evidence-based studies and implement an individualized treatment and health-care plan by sharing information with potential users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…It was 51 in western societies [13]. A study conducted by Sahin et al revealed that mean menopause age for 729 females was 47±4.8 [14]. We revealed similar results in our study.…”
Section: Discussionsupporting
confidence: 90%
“…It was 51 in western societies [13]. A study conducted by Sahin et al revealed that mean menopause age for 729 females was 47±4.8 [14]. We revealed similar results in our study.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, it has been reported that Asian, Arabian, and African women perceive menopause more positively and have a more smooth and comfortable period (Huang et al, 2010; Makuwa et al, 2015; Odıarı and Chambers, 2012). In a qualitative study conducted by us at the same hospital in Turkey and in similar studies conducted in Turkey, it has been shown that women mostly perceive menopause negatively (Alan et al, 2016; Sahin et al, 2011; Yangın et al, 2010). As a result, when a woman goes through menopause, menopause can be regarded as an unfavorable period for herself with the negative perceptions such as the end of fertility, the beginning of getting older, and the end of sexuality.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the incidence of GSM was high in women who perceived menopause as negative. In Turkish society, menopause is negatively perceived by women [27, 32-34]. Yanikkerem et al .…”
Section: Discussionmentioning
confidence: 99%